Lung epithelial wound healing in health and disease. (October 2010) - Gardner, Aaron; Borthwick, Lee A; Fisher, Andrew J
Physiological lung epithelial wound repair is a complex, highly orchestrated process presenting numerous points where dysregulation may occur, leading to the development of several pulmonary disorders. Current studies are limited by a lack of relevant lung injury models, with much work relying on other organ models such as the skin or in vitro cultures. However, much promising investigative work is being undertaken, some of which is described in this article. This article attempts to describe the processes required to heal a severe wound to the airway epithelium, characteristic of several chronic pulmonary disorders, highlighting areas where dysregulation may occur, which in turn leads to the development or continuation of a disease state.